The Influence of economic growth, exchange rate, and inflation on foreign tourist visits to Indonesia - Rifai, Nila; Kurniawan, Taufiq (Publisher of Widyagama University of Malang (UWG Press), 2023)
Tourism is one of the economic sectors that can quickly bring in foreign exchange for the country if managed properly and sustainably. Many economic variable factors influence the demand and supply of the tourism industry, especially the level of foreign tourist visits, such as economic growth, exchange rate, and inflation. This study aimed to determine the influence of economic variable factors, especially economic growth, exchange rate, and inflation, on the number of foreign tourist visits in Indonesia. A quantitative descriptive method is used in this study. To analyze the factors influencing the number of foreign tourist visits in Indonesia, independent variables such as economic growth, exchange rate, and inflation are used in the Multiple Linear Regression equation model. The data used in this study is secondary data on annual time series for the period 2001 â€“ 2020. The research result shows that the number of foreign tourist visits in Indonesia is significantly influenced by economic growth and the exchange rate, while inflation has no significant effect. There are still other factors (non-economic) that influence the decision of tourists to visit. Several factors that need to be considered to increase the interest of foreign tourists visits in Indonesia are tourist attractions, accessibility, amenities, ancillary, attractive promotions, and social, political, and security stabilityJEL ClassificationÂ A13; B55; D69